Carboxymethylation of Starches Obtained from Three Dioscorea Species: Effect on Powder, Granule and Tablet Properties - Nnamdi, Jolly A.; Nnamdi, Jolly A.; Arhewoh, Matthew I.; Eraga, Sylvester O.; Iwuagwu, Magnus A. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Excipients used in tablet production can be modified to enhance tablet properties. The aim of this study was to prepare carboxymethyl starch (CMS) using starches obtained from three Dioscorea (yam) species viz D. rotundata, D. dumetorum and D. alata, and to investigate the effect of carboxymethylation on their powder, granules and tablet properties. Comparative evaluation studies were carried out on the native and modified starch powders. Fourier Transform Infrared Spectrophotometry (FTIR) and Differential Scanning Calorimetry (DSC) were carried out on the powders to ascertain carboxymethylation. The properties of paracetamol granules and tablets obtained from the powders were analyzed according to official methods. The modified and native starches were comparable in powder micromeritics, bulk and flow properties. The modified starches exhibited superior swelling capacity of 3.2-14.4 % above the native starches. Granule properties were influenced by the concentration of starch incorporated as disintegrant. The FTIR and DSC spectra confirmed changes in functional groups. Tablet hardness ranged from 5.62 to 16 N while disintegration was achieved in < 3 min. Excellent disintegrant was obtained at 5 %w/w CMS in paracetamol tablet formulation. The modified starch will find usefulness as enhanced disintegrant in compressed tablet dosage forms especially where shorter disintegration times are desired as a result of its superior swelling capacity.